2020
DOI: 10.1103/physrevresearch.2.013082
|View full text |Cite
|
Sign up to set email alerts
|

Near-ideal molecule-based Haldane spin chain

Abstract: The molecular coordination complex NiI2(3,5-lut)4 [where (3,5-lut) = (3,5-lutidine) = (C7H9N)] has been synthesized and characterized by several techniques including synchrotron X-ray diffraction, ESR, SQUID magnetometry, pulsed-field magnetization, inelastic neutron scattering and muon spin relaxation. Templated by the configuration of 3,5-lut ligands the molecules pack in-registry with the Ni-I· · · I-Ni chains aligned along the c-axis. This arrangement leads to through-space I· · · I magnetic coupling which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…NiI 2 (3,5-lut) 4 has been previously characterized by Williams et al 19 and exhibits easy-axis single-ion anisotropy with D = −1.2(3) K, which was extracted from inelastic neutron scattering measurements. Pulsed-field magnetization shows a very high saturation field relative to the other compounds reported here, indicating strong antiferromagnetic interactions of J = 17.5(1) K along the Ni–I···I–Ni chains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NiI 2 (3,5-lut) 4 has been previously characterized by Williams et al 19 and exhibits easy-axis single-ion anisotropy with D = −1.2(3) K, which was extracted from inelastic neutron scattering measurements. Pulsed-field magnetization shows a very high saturation field relative to the other compounds reported here, indicating strong antiferromagnetic interactions of J = 17.5(1) K along the Ni–I···I–Ni chains.…”
Section: Resultsmentioning
confidence: 99%
“…The complete phase diagram for these systems displays Ising and XY -ordered states along with two gapped phases: the Haldane and quantum paramagnetic states (see Figure ). It has already been shown that NiI 2 (3,5-lut) 4 is a highly isotropic [ D / J = −0.07(1)] example of a Haldane chain . In addition, because it displays no magnetic order even when the Haldane gap has been closed by the application of an applied magnetic field, the value of J ⊥ in this material is believed to be extremely small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dipole fits performed by SquidLab are shown as black lines through the background subtracted data. The example samples shown are (a) an S = 1 1D molecule-based magnet [11], with low density of magnetic ions, dispersed in the pressure medium of a piston-cylinder pressure cell (Quantum Design and partners), (b) diamagnetic sample Pd 3 P 2 S 8 mounted on a standard quartz sample holder and (c) a molecular framework antiferromagnet pressed pellet within a pressure cell (Camcool Research Ltd) [12]. In all these cases there is no evident dipole in the raw data at the sample position and hence fitting and extraction of the magnetic moment is not possible.…”
Section: Examples and Demonstrationsmentioning
confidence: 99%
“…The remarkable difference between one-dimensional (1D) AFM systems of integer and halfinteger spins opens a highly successful avenue in understanding the low-dimensional strongly correlated electronic materials. The isotropic Heisenberg AFM model has been unexpectedly coined in a number of nearly ideal quasi-one-dimensional materials such as Cu(C 4 H 4 N 2 )(NO 3 ) 2 [17], Sr 2 Cu(PO 4 ) 2 [18], KCuF 3 [19], CuSO 4 ⋅5D 2 O [20], and spin-1 chain materials like SrNi 2 V 2 O 8 [21,22], Ni(C 2 H 8 N 2 ) 2 NO 2 (ClO 4 ) [23,24] and * wlyou@nuaa.edu.cn NiI 2 (C 7 H 9 N) 4 [25]. There have also been attempts to realize spontaneous symmetry breaking and develop true AFM order in spin-1/2 Heisenberg chains.…”
Section: Introductionmentioning
confidence: 99%